Editorial Programs in Transition: Post-Socialist Era Hungarian Publishing Houses in Romania - Ágnes Gálfalvi (Symbolon, 2023)
The tradition continued to be important, though the controversial issue of Hungarian book publishing in Romania following the 1989 changes from a socialist to a market economy and from a dictatorship to a democracy. While before 1989 the Hungarian publishing scene was largely dominated by one publishing house, Kriterion, during a period of transition it gradually diversified both structurally and in the way of editorial programs. Cultural traditions, the quality as well as the number of available manuscripts and the reading public’s expectations on the one hand, and financial and logistical circumstances on the other were some of the main factors that determined editorial programs in the transitional era. Pre-1989 Kriterion’s editorial program seems to have been a benchmark for budding publishing houses in many respects; however, there are also a number of positive/negative divergences. My paper examines the extent to which, after the regime change, Hungarian publishing houses in Romania continue and/or break the traditions established by former editorial boards, also, it presents the circumstances that influenced editorial programs in the new era.